(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Professional activities of individuals under stressful conditions affect their psychic processes and capability to work. The social-cognitive distortions developing under these conditions require a comprehensive assessment involving, particularly, quantitative assessment. The relevant psychometric instruments for detecting these distortions should be carefully psychometrically adapted. Purpose: To analyze psychometrically the scales for assessing the test-taking attitudes in individuals under stressful situations, and to determine associations between response distortions and perceptual distortions. Material and Methods: The study sample consisted of 286 eye care workers from the Filatov Institute of Eye Diseases and Tissue Therapy. The study was conducted with the use of the Minnesota Multiphasic Personality Inventory by Hathaway and McKinley and Wartegg Drawing Completion Test. Results: We found that in stressful situations, social-cognitive distortions are accompanied by visual perceptual distortions. Particularly, we found that the desire of the responder to appear in a socially better light than he or she actually is, is associated with the tendency of faulty ignorance of large visual stimuli, which may be considered as co-manifestations of selective visual perception and response distortions. In addition, distortions in stressful situations were associated with both conscious and unconscious levels of psyche. We believe the modified L scale may be used in practice for assessing perceptual distortions and stress-related disorders like psychosomatic disorders and post-traumatic stress disorders.